Improving acid resistance and characteristics of microencapsulated Lactobacillus brevis RK03 using top fluid bed drying technology. (November 2021) - Wu, Chien-Hui; Liu, Yu-Ching; Ou, Shih-Fu; Chen, Shyi-Tien; Kuo, Jen-Min; Hsueh, Yi-Huang
Graphical abstract: Highlights: Carriers increase bacterial viability during drying of probiotics. Optimized top fluid bed drying conditions yielded high cell survival rates. Whey protein improved bacterial resistance to gastrointestinal conditions. Whey protein enhanced dispersibility, solubility, stability of bacterial powder. Abstract: Thermoprotective carrier agents increase bacterial viability during the drying process. We investigated the ability of various carriers, including skim milk powder, casein, and whey protein, to improve the survival rate of Lactobacillus brevis RK03 under gastrointestinal tract conditions. Employing optimized top fluid bed drying (TFBD) conditions (40 min at 50 °C), the highest bacterial survival rate (95 %) was achieved using casein and whey protein as carriers for RK03. Additionally, whey protein-microencapsulated RK03 displayed the highest survival rates in gastric juice at pH 3.0 (96 %) and 2.0 (75 %). Further, whey protein-microencapsulated RK03 exhibited better dispersibility and solubility than RK03 microencapsulated with other carriers, displayed a slower degradation rate at 50 °C and 60 °C, and had the lowest activation energy (30.27 J/mol). These results indicate that the use of whey protein as a carrier during TFBD is suitable for the production of RK03 probiotic powder.